PERBANDINGAN VOLUME ABU SEKAM PADI DAN TANAH GAMBUT SEBAGAI MEDIA DAN PEMBERIAN UREA UNTUK PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TAHAP PRENURSERY - Hendra Syaputra; Mokhamad Irfan; Bakhendri Solfan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
The research was conducted from March until June 2012 at Sudirman regency Estate No. 2, Datuk Setia Maharaja/Parit Indah street, the village of Tangkerang Selatan, sub-district of Bukit Raya Pekanbaru. The objective of research was to find the volume ratio of rice husk ash and peat soil as a media and application of urea for seed growth of oil palm (Elaeis guineensis jacq.) at prenursery stage. The experimental was randomized block design with two factors and three replication. The first factor was the volume ratio of rice husk ash and peat soil which consisted on five level namely 0:1, 1:0, 1:1, 2:1, 3:1, and the second factor was application of urea consisted of four level namely 0%, 0,1%, 0,2%, 0,3%. Variables of the research were pH, plant height, stem diameter, the number of midrib, fresh weight of plant, dry weight of plant, and leaf color. Results of the research showed that application media treatment affected significantly plant height, stem diameter, the number of midrib, fresh weight of plant, dry weight of plant, and leaf color, and the application of urea affected stem diameter and the number of midrib. The optimum volume ratio between rice husk ash and peat soil was 2.07:1 for plant height, 1.90:1 for number midrib , 1.22:1 for stem diameter, 1.49:1 for fresh weight of plant, 1.37:1 for dry weight of plant, and the media of peat soil was better than husk ash. Optimum dosage of urea was 0.3% for stem diameter and number of midrib variables.